A review of the hyperiidean amphipod family Cystisomatidae Willemöes-Suhm, 1875 (Crustacea: Amphipoda: Hyperiidea) - Zeidler, Wolfgang (Zootaxa, 2003)
A taxonomic review of the hyperiidean amphipod family Cystisomatidae is presented, based on material held by most of the major museums in the world. A new superfamily, Cystisomatoidea, is proposed to accommodate the family Cystisomatidae, based on the unique method of brooding the young, the remnant second antennae in both sexes, and other minor characters inconsistent with the superfamily Vibilioidea in which it was placed previously. The family is currently monogeneric and six species of Cystisoma are recognised in this review, including one described as new to science. The new species, C. gershwinae sp. nov., is recorded from the tropical regions of the Atlantic, western Pacific and Indian Oceans, including the Indo-Pacific region. A key to all species is provided. Two species, C. spinosus (Fabricius, 1775) and C. neptunus Guérin-Méneville, 1842, are considered nomen dubia.